Preparation of Novel Bridged Bicyclic Thiomorpholines as Potentially Useful Building Blocks in Medicinal Chemistry - Walker, Daniel P.; Rogier, D. Joseph (Synthesis, 2013)
Thiomorpholine and thiomorpholine 1,1-dioxide are important building blocks in medicinal chemistry research, and some analogues containing these moieties have entered human clinical trials. Analogues containing bridged bicyclic thiomorpholines have also shown interesting biological profiles. 3-Thia-6-azabicyclo[3.1.1]heptane, 3-thia-8-azabicyclo[3.2.1]octane, and their corresponding 1,1-dioxide counterparts were prepared as novel bicyclic thiomorpholine building blocks. Each heterocycle was synthesized from an inexpensive starting material by straightforward chemistry.
Keywords: stereoselective synthesis; heterocycles; bicyclic compounds; pyrroles; hydrogenation